Neuroinflammation in neurodegeneration via microbial infections - Tran, Van Thi Ai; Lee, Luke P.; Cho, Hansang (Frontiers in Immunology, 2022)
Recent studies address that microbial infection induces neurodegeneration in human brains. However, the underlying mechanisms are still not precise due to the complexity of multicellular and multiorgan interactions. In this review, we describe how pathogens can cause neurodegeneration either directly or via neuroinflammation. Firstly, three inter-organ communications were highlighted as the routes for pathogens to enter the brain: nose-brain axis, lung-brain axis, and gut-brain axis. Next, we described the crosstalk of the central immunity upon pathogenic infection. Lastly, our study indicates that neuroinflammation as a critical player in pathogen-mediated neurodegeneration. Taken together, our study envisions antibiotics targeting neuro-pathogens could be a potential therapeutic strategy for neurodegenerative diseases.